2017
DOI: 10.1038/s41598-017-17329-7
|View full text |Cite
|
Sign up to set email alerts
|

A re-engineered immunotoxin shows promising preclinical activity in ovarian cancer

Abstract: RG7787 is a re-engineered mesothelin-targeted immunotoxin with reduced immunogenicity composed of a humanized anti-mesothelin Fab fragment and a B-cell epitope silenced 24 kD fragment of Pseudomonas exotoxin A. High prevalence of mesothelin-positive cases and a large unmet medical need make ovarian cancer a promising indication for the clinical development of RG7787. However, ovarian cancer patients also frequently have elevated serum levels of the cancer antigen 125 (CA-125). In principle this could pose a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The cytotoxicity and antitumor effects of LMB-100 were verified on different cancer types including breast ( 126 ), gastric ( 126 ), lung ( 127 ), ovarian ( 128 ), and colorectal ( 129 ) cancers, as well as pancreatic ductal adenocarcinoma ( 130 133 ). Almost all cell lines corresponding to these malignancies were affected by LMB-100 at concentrations in the picomolar range (as low as 6.8 pmol/lit) ( 130 133 ).…”
Section: Pseudomonas Exotoxin Amentioning
confidence: 99%
“…The cytotoxicity and antitumor effects of LMB-100 were verified on different cancer types including breast ( 126 ), gastric ( 126 ), lung ( 127 ), ovarian ( 128 ), and colorectal ( 129 ) cancers, as well as pancreatic ductal adenocarcinoma ( 130 133 ). Almost all cell lines corresponding to these malignancies were affected by LMB-100 at concentrations in the picomolar range (as low as 6.8 pmol/lit) ( 130 133 ).…”
Section: Pseudomonas Exotoxin Amentioning
confidence: 99%
“…7 Besides, due to unique combination of high expression in different solid tumors and its complete lack of vital normal tissues, MSLN is being widely desirable for tumor-selective toxic payload delivery and tumor immunotherapy approaches. 20 Numerous research has investigated serum MSLN as a diagnostic marker for EOC; [21][22][23][24][25][26][27][28][29] however, very few studies have investigated tumor MSLN gene expression in EOC, and to date, no report has addressed its level in peritoneal fluid (PF) of ovarian cancer patients. In this study, we comprehensively investigated tumor MSLN gene expression and the plasma and PF MSLN level in EOC patients with different clinicopathological features including FIGO staging (FIGO I-IV), Shimizu-Silverberg grading (grades I-III), histological type of tumor (serous, mucinous, endometrioid, and undifferentiated), and Kurman and Shih type of EOC (types 1 and 2).…”
Section: Introductionmentioning
confidence: 99%
“…7 Besides, due to unique combination of high expression in different solid tumors and its complete lack of vital normal tissues, MSLN is being widely desirable for tumor-selective toxic payload delivery and tumor immunotherapy approaches. 20…”
Section: Introductionmentioning
confidence: 99%
“…When combined with cytotoxic chemotherapy, tumor regressions were seen in mesothelioma xenograft models [ 71 ]. Kollmorgen et al found that the combination of LMB-100 and cisplatin or paclitaxel showed striking tumor growth inhibition in a PDX model of ovarian cancer as well [ 73 ]. Furthermore, synergistic activity was observed with taxanes, such that the combination produced complete tumor responses in a mouse model of pancreatic cancer [ 74 ].…”
Section: Pre-clinical Development Pipelinementioning
confidence: 99%